2015
DOI: 10.1097/pcc.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Delirium and Associated Risk Factors

Abstract: Objective To describe a single-institution pilot study regarding prevalence and risk factors for delirium in critically ill children. Design A prospective observational study, with secondary analysis of data collected during the validation of a pediatric delirium screening tool, the Cornell Assessment of Pediatric Delirium (CAPD). Setting This study took place in the pediatric intensive care unit (PICU) at an urban academic medical center. Patients 99 consecutive patients, ages newborn to 21 years. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 32 publications
6
73
1
Order By: Relevance
“…Our findings are consistent with those of prior single-center studies which reported PD rates ranging from 10–30%(14,15,18,20,25). Children requiring MV (likely with an increased exposure to sedatives and higher severity of illness) had a delirium prevalence of 53%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with those of prior single-center studies which reported PD rates ranging from 10–30%(14,15,18,20,25). Children requiring MV (likely with an increased exposure to sedatives and higher severity of illness) had a delirium prevalence of 53%.…”
Section: Discussionsupporting
confidence: 93%
“…PD has been associated with severity of illness, age less than 5 years, sedation, and mechanical ventilation (MV)(18–20). PD has been linked to significant increase in hospital length of stay, and post-traumatic stress symptoms and delusional memories in child survivors(18,21,22). However, most PD research has been limited by retrospective design, narrow inclusion criteria, small number of subjects, and single-center studies(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with severe postoperative delirium experienced a longer duration of mechanical ventilation and length of stay, and this has been seen in previous studies [8, 9]. However, delirious patients did not have a higher severity of illness, which differs from a previous report showing that delirium was associated with a higher PRISM score [10].…”
mentioning
confidence: 53%
“…(1) Furthermore, pediatric specific risk factors and outcomes associated with delirium have not been well delineated, though a recent study reveals that patient factors such as developmental delay, duration of mechanical ventilation, and age are associated with delirium during critical illness. (2) Similarly, the underlying mechanism of pediatric delirium has yet to be fully realized and therefore many aspects of delirium management remain in the exploratory phase. These very important but undefined areas of delirium within the very young also remain poorly described in the elderly, particularly in patients with delirium superimposed on dementia.…”
mentioning
confidence: 99%